Light-induced aggregation of microbial exopolymeric substances. (August 2017) - Sun, Luni; Xu, Chen; Zhang, Saijin; Lin, Peng; Schwehr, Kathleen A.; Quigg, Antonietta; Chiu, Meng-Hsuen; Chin, Wei-Chun; Santschi, Peter H.
Abstract: Sunlight can inhibit or disrupt the aggregation process of marine colloids via cleavage of high molecular weight compounds into smaller, less stable fragments. In contrast, some biomolecules, such as proteins excreted from bacteria can form aggregates via cross-linking due to photo-oxidation. To examine whether light-induced aggregation can occur in the marine environment, we conducted irradiation experiments on a well-characterized protein-containing exopolymeric substance (EPS) from the marine bacterium Sagitulla stellata . Our results show that after 1 h sunlight irradiation, the turbidity level of soluble EPS was 60% higher than in the dark control. Flow cytometry also confirmed that more particles of larger sized were formed by sunlight. In addition, we determined a higher mass of aggregates collected on filter in the irradiated samples. This suggests light can induce aggregation of this bacterial EPS. Reactive oxygen species hydroxyl radical and peroxide played critical roles in the photo-oxidation process, and salts assisted the aggregation process. The observation that Sagitulla stellata EPS with relatively high protein content promoted aggregation, was in contrast to the case where no significant differences were found in the aggregation of a non-protein containing phytoplankton EPS between the dark and light conditions. This, together with the evidence that protein-to-carbohydrate ratio of aggregates formed under light condition is significantly higher than that formed under dark condition suggest that proteins are likely the important component for aggregate formation. Light-induced aggregation provides new insights into polymer assembly, marine snow formation, and the fate/transport of organic carbon and nitrogen in the ocean. Graphical abstract: Highlights: Sunlight can induce aggregation of bacterial exopolymeric substances. Reactive oxygen species played critical roles in the photo-oxidation process. First study that pinpoints proteins as likely components taking part in light-induced aggregation in the marine environment. New insights into polymer assembly, marine snow formation, and the fate of organic carbon and nitrogen in the ocean.